2022
DOI: 10.1186/s12936-022-04331-2
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in pregnancy control and pregnancy outcomes: a decade’s overview using Ghana’s DHIMS II data

Abstract: Background Malaria in pregnancy control interventions have been implemented through antenatal care services for more than 2 decades in Ghana. The uptake of these interventions has seen steady improvement over the years. This has occurred within the context of decreasing global trends of malaria infection confirmed by decreasing malaria in pregnancy prevalence in Ghana. However, not much is known about how these improvements in interventions uptake and reduction in malaria infection prevalence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Fetal deaths in Ghana, in contrast, were found to be associated with fetal infections in 9.7% to 13.0% of cases [ 3 , 4 ] and placental inflammation in up to 24.8% of cases [ 4 ]. As repeatedly demonstrated, viral, bacterial, mycobacterial and parasitological infections threaten the health of mother and fetus [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For Ivory Coast, fewer respective studies have been published, but available data nevertheless indicate relevant pregnancy-associated infection risks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal deaths in Ghana, in contrast, were found to be associated with fetal infections in 9.7% to 13.0% of cases [ 3 , 4 ] and placental inflammation in up to 24.8% of cases [ 4 ]. As repeatedly demonstrated, viral, bacterial, mycobacterial and parasitological infections threaten the health of mother and fetus [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For Ivory Coast, fewer respective studies have been published, but available data nevertheless indicate relevant pregnancy-associated infection risks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings contrast with those from a trend analysis of Ghana’s DHIMS 2 data that showed the prevalence of anaemia at term was persistently lower than at booking in the 10-year period from 2012 to 2021. 21 It is not immediately clear why the present study showed an increase in anaemia prevalence between booking ANC visit and 36–40 weeks but the findings provoke important questions on other contributors to maternal anaemia aside malaria infection, ITN use and uptake of IPTp-SP. The study did not take into consideration morbidities such as helminthiasis, sickle cell disease and other haemoglobinopathies, human immunodeficiency virus infection, schistosomiasis and others that could impact on maternal anaemia.…”
Section: Discussionmentioning
confidence: 55%
“…Approximately 84% of the study women received optimal IPTp-SP doses in their last pregnancy. This is higher than national level reports of 55.0% in 2021 from Ghana’s district health information management systems database (DHIMS 2) 21 and the 61% reported in the 2019 malaria indicator survey. 27 This may be due to differences in the denominator for computing these measures.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Vulnerable groups outside of early childhood include women with approximately one-third of the 40 million pregnancies in Africa affected. Malaria in pregnancy and early childhood is associated with anemia 2 4 , severe disease, poor birth outcomes (low birth weight, prematurity, and stillbirth), and has an adverse socio-economic impact. Until recently, public health measures targeting malaria control and elimination were primarily limited to long-lasting insecticide-treated bed nets, intermittent preventive treatment, and chemoprevention.…”
Section: Introductionmentioning
confidence: 99%